The effect of bariatric surgery in comparison with the control group on the prevention of comorbidities in people with severe obesity: a prospective cohort study - Amir Ebadinejad; Maryam Barzin; Behnaz Abiri; Maryam Mahdavi; Alireza Khalaj; Danial Ebrahimi; Farhad Hosseinpanah; Majid Valizadeh (BMC Surgery, 2022)
Abstract Background Obesity is a global health priority, particularly in developing countries. The preventive effect of bariatric surgery against obesity-related diseases in the developing countries of the Middle East and North Africa region, where type 2 diabetes mellitus (T2DM), hypertension (HTN), and dyslipidemia prevail, has not been examined. Method Severely obese participants who underwent bariatric surgery were compared with their counterparts who underwent no intervention. These patients had been followed up in two prospective cohort studies for three years. We here determined the incidence of new-onset T2DM, HTN, and dyslipidemia and reported absolute and relative risks for the incidence of these comorbidities in the two groups. Results In this study, 612 participants in the bariatric surgery group were compared with 593 participants in the control group. During the follow-up period, T2DM developed in eight (2.9%) people in the surgery group and 66 (15.0%) people in the control group (P < 0.001). New-onset HTN and dyslipidemia showed significantly lower frequencies in the surgery group compared to the control group (4 (1.8%) vs. 70 (20.4%) and 33 (14.3%) vs. 93 (31.5%), respectively). Regarding a less favorable metabolic profile in the surgery group at the baseline, the relative risk reductions associated with bariatric surgery were 94, 93, and 55% for the development of T2DM, HTN, and dyslipidemia, respectively. Conclusion The risk reduction of obesity-related comorbidities after bariatric surgery should be considered in the decision-making process for public health in the region, which bariatric surgery could result in the prevention of comorbidities.